2019
DOI: 10.1038/s41467-019-11112-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of polygenic risk score usage and performance in diverse human populations

Abstract: A historical tendency to use European ancestry samples hinders medical genetics research, including the use of polygenic scores, which are individual-level metrics of genetic risk. We analyze the first decade of polygenic scoring studies (2008–2017, inclusive), and find that 67% of studies included exclusively European ancestry participants and another 19% included only East Asian ancestry participants. Only 3.8% of studies were among cohorts of African, Hispanic, or Indigenous peoples. We find that predictive… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

38
772
1
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 845 publications
(818 citation statements)
references
References 51 publications
38
772
1
7
Order By: Relevance
“…One major limitation is that the majority of participants in GWAS used to derive PRS are of European ancestry 8,9 . Although many genome-wide significant GWAS hits do replicate in non-European ancestry cohorts 1014 , overall the predictive power of PRS is lower and decreases with genetic distance from Europeans 1518 . There are many possible explanations for this, including inter-cohort differences in data collection, phenotype or environment, differences in linkage disequilibrium (LD) structure or allele frequencies across populations 19 , differences in causal or marginal effect sizes, and epistatic or gene-environment interactions 20 .…”
Section: Introductionmentioning
confidence: 99%
“…One major limitation is that the majority of participants in GWAS used to derive PRS are of European ancestry 8,9 . Although many genome-wide significant GWAS hits do replicate in non-European ancestry cohorts 1014 , overall the predictive power of PRS is lower and decreases with genetic distance from Europeans 1518 . There are many possible explanations for this, including inter-cohort differences in data collection, phenotype or environment, differences in linkage disequilibrium (LD) structure or allele frequencies across populations 19 , differences in causal or marginal effect sizes, and epistatic or gene-environment interactions 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Polygenic risk scores (PRSs) have successfully shown their predictive ability to idenitify those with a several-fold higher inherited risk of a given disease or condition 2 . Both an increase in statistical power and ethnic diversity in genetic studies—accelerated by nation-wide biobanks—have been instrumental in accurately predicting disease onset by PRSs 36 . Stratification of health risks based on PRSs would be one of the strategies to improve population health through targeted prevention.…”
Section: Introductionmentioning
confidence: 99%
“…Common variant gene scoring approaches have limited trans-ancestral predictive value and clinical implications remain highest when discovery and validation sets are ethnically matched, which is largely the case only for European populations 18,19,23 . Moreover, empirical and simulation models have demonstrated that directional selection across ancestries can severely impair predictive accuracy in non-European validation populations, even after accounting for principal components and proportion of causal variants 18,19 .…”
Section: Discussionmentioning
confidence: 99%